Labour Market Flexibilization and Income Distribution in Europe - Arestis, Philips; Ferreiro, Jesús; Gómez, Carmen (Panoeconomicus, 2021)
This paper analyses the role played by the flexibilization of labour markets on functional income distribution. Specifically, we analyse whether employment protection legislation affects the evolution of labour income share, measured by the size of compensation of employees as a percentage of GDP, the sum of wages and salaries as a percentage of GDP and the size of the adjusted wage share, in twenty European economies. Our study’s results show that the evolution of labour income share is explained by the economic growth, the growth of employment and unemployment rates, and the growth of real wages. Regarding the role played by the flexibility of the labour market, and specifically of the employment protection legislation, only employment protection for temporary workers has a significant impact on the evolution of labour shares. Our results show that stricter provisions on the use of fixed-term and temporary agency contracts have a positive impact on the growth of labour shares. Key words: Employment protection legislation, Labour markets, Labour income share, Income distribution. JEL: C33, E24, E25, F66.